Pengaruh Komunikasi dan Motivasi terhadap Kinerja Pegawai Pada UPT. Samsat Medan Selatan - Rizki, Nur; Pane, Sri Gustina; Pinem, M. Nelson (Universitas Islam Islam Sumatera Utara, 2023)
The study is titled The Influence of Communication and Motivation on Employee Performance at UPT. Samsat Medan Sekatan. The formulation of the problem in this study is how the influence of commuication and motivation on the work of employees of UPT. Samsat Medan Selatan. This study aims to find out how Communication and Motivation Affect UPT. Samsat Medan Selatan. This study aims to determine the influence of communication and motivation on Employee Performance at UPT. Samsat Medan Selatan. The data analysis techniques in this study are descriptive analysis and multiple linear regression analysis. The sample in the study consisted of 59 employees. The analytical technique used is the quantitative method. The results of this study showed that communication variables had a positive and significant effect on the performance employees of UPT. Samsat Medan Selatan. Motivation variables have a positive and significant effect on the performance employees of UPT. Samsat Medan Selatan. Communication and Motivation variables have a positive and significant effect on the performance emplouees of UPT. Samsat Medan Selatan